Derivation of Regression Coefficients and Conversion Factors for 1-Minute Rain Rate Statistics in A Tropical Environment - Igwe, K. C. (Journal of Advanced Industrial Technology and Application, 2023)
An important characteristic of rainfall levels at a particular place is the statistical distribution of rainfall rate. In this paper, 1-minute, 5-minute and 30-minute integration time rainfall data were obtained from various weather stations in the Physics Department of Federal University of Technology, Minna, North Central Nigeria. The essence is to derive conversion factors that can be used to predict 1-minute integration time rainfall rate from rainfall rates of other integration times. The results obtained revealed that a power law relationship exist between 1-minute (R1) and the equiprobable 5-minute rain rate (R5), derived as R1 = 1.414 R51.640; and between 1-minute (R1) and the equiprobable 30-minute rain rate (R30), derived as R1 = 0.960 R301.897. Also, conversion factors Ce and CR for 1-minute rain rate statistics were derived. The conversion factors Ce derived for T = 5-minute and ? = 1-minute are 1.08, 1.05, 0.98 and 1.04 respectively for 40 mm/h, 60 mm/h, 80 mm/h and 100 mm/h rain rates, while the conversion factors CR derived for ? = 1-minute as against T = 5-minute are 0.70 and 0.71 for R0.01 = 70 mm/h and R0.001 = 100 mm/h respectively. In addition, the CR derived for ? = 1-minute as against T = 30-minute are 0.06 and 0.25 for R0.01 = 6 mm/h and R0.001 = 35 mm/h respectively.